Benthic foraminiferal fauna from anoxic sediments in the Kveithola Trough, northwest Barents Sea (Arctic region). - Gamboa Sojo VM.; Morigi C.; Lucchi RG.; Caridi F.; Sabbatini A.; and the Scientific Party of BURSTER cruise (country:ITA, 2019)
The recent sedimentary records preserve the imprint of the climatic changes in the last decades. One of the most sensitive region to these changes is the Arctic region, as it responds more rapidly to global warming than most of the other areas on our planet. The Kveithola Trough, in the NW Barents Sea, represents an important repository of the history of the past climatic changes affecting the local oceanographic configuration and ice sheet evolution. Indeed this zone is characterized by the interaction of two main water masses: the cold, fresh Arctic Water coming from the north and the warm, salty Atlantic Water flowing from the south. During the oceanographic cruise EUROFLEETS2-BURSTER (June 2016), seven multi-cores were collected from three sampling sites in the Kveithola Trough area. The aim of this study is to analyze three of these cores focusing on dead and living benthic foraminiferal assemblages and sedimentological parameters, in order to study the past variability and present conditions of the water masses, the organic matter flux and oxygen concentration to the sea floor during the last decades. A total of 77 dead benthic species (calcareous perforated, miliolids and agglutinated) and 78 living (50 species of calcareous perforated, miliolids and agglutinated, plus 28 species of soft-shelled) foraminiferal species were identified. The dominant (live and dead) foraminiferal species are Globobulimina auriculata, Globobulimina arctica, Nonionellina labradorica, Cassidulina laevigata, and Cassidulina neoteretis, present in different percentages at each site. Benthic foraminiferal assemblages allow to distinguish different (palaeo)- environmental conditions along the study area. The preliminary results shows that during the last 200 years until present, the deeper part of the Kveithola trough has been a highly dynamic environment. The inner part is a stressful environment with low oxygen concentrations and high superficial phytodetritus influx, likely influenced by methane seepage. A higher influence of ...